Application of harmonic balance method to aerodynamic characteristics prediction of spinning vehicle. Issue 2 (6th March 2017) - Lu, Tianyu; Lei, Juanmian; Wu, Xiaosheng; Yin, Jintao
Abstract : Purpose: The purpose of this paper is to examine the ability of the harmonic balance method for predicting the aerodynamic characteristics of rigid finned spinning vehicle. Design/methodology/approach: The aerodynamic characteristics of a rigid four-finned spinning vehicle at Mach number 2.5 and angle of attack of 20 degrees are simulated using the harmonic balance method and the unsteady time-accurate approach based on the dual-time method. The numerical results are analyzed, and the computed aerodynamic coefficients of the harmonic balance method are compared with those of the dual-time method. The influence of the number of harmonics is presented. The computed Magnus force and moment coefficients are compared with the experimental data. The flow fields at different roll angles are presented. The computational efficiency of harmonic balance method is analyzed. Findings: The results show that the aerodynamic coefficients of spinning vehicle could be predicted by the harmonic balance method with reasonable accuracy compared with the dual-time method. For the harmonic balance method, the accuracy of the computed leeward side flow is relatively poor compared with that of the computed windward side flow. Meanwhile, the computational efficiency is influenced by initial guess and the intensity of unsteady effect. Practical implications: The harmonic balance method could be used for the aerodynamic prediction of spinning vehicle, which may improve the efficiency of vehicle design. Originality/value: This paper presents the results of the harmonic balance method for simulating the aerodynamic characteristics of finned spinning vehicle. The accuracy and efficiency of the method are analyzed.